Effect of storage duration and analyte concentration on measurement of neutral pH clinical chemistry urine analytes - Debnath, Chapal; Savaliya, Niral (International Journal of Research in Medical Sciences, 2021)
Background: The aim of the study was focused very keenly in measuring the changes in concentration of sodium, potassium and creatinine in urine, stored for 60 days effect of urinary storage duration of clinical chemistry analytes. This study determined whether patient urine samples can be used for day to day urine quality control. Methods: Spot urine samples were collected from left over samples from the admitted patients in various hospital wards. The samples are kept which its pH was unaltered or unspiked and was aliquoted and deep fridged immediately. These aliquots were melted at an incubator temperature of 86 ºC and was analyzed in the analyzer for 60 days and data were collected for checking variations. Results: With the strenous and continious monitoring from the side of the researchers, the researchers had throughly analysed and found that in both the sets almost all of those analysed urine test of pH 5 and analytes remained very much stable for a period of 60 days which could be used for running daily internal quality controls. Conclusions: Patient urine can be used as internal quality control sample for at least 60 days for sodium, potassium and creatinine. During the 60 days period, there is no appreciable degradation of any of the two sets of samples for sodium, potassium and creatinine measurements.